Using English and Indonesian in Increasing Students' Understanding and Knowledge in Science Lessons - Henny Sanulita (LPPM Undiksha, 2024)
The Indonesian Ministry of Education has introduced the basis for teaching Science and Mathematics in English. However, the learning outcomes obtained by students in science learning are still superior when using Indonesian compared to English. Even though English dominates all learning sources. This is an urgent matter to research because there is a gap between theory, expectations, and facts in the field. The aim is to analyze the impact of language on student achievement in science subjects by correlating two tests with different languages (English and Indonesian) on one measurement scale. The research method uses a survey. The research subjects were junior high schools, numbering 1000 people. Data collection techniques use test instruments and analysis techniques use the Test Analysis Program (TAP). Results and Findings show that changes in language policy, the Indonesian Examinations Institute, and the Indonesian Examinations Council use bilingual examinations for the learning process and assess subjects for all levels much better. It was found that student achievement on the Indonesian version of the test was still better than the English version of the test. The implications for the learning process in schools are fully using Indonesian in implementing the material taught compared to using English.